Kinetic and mechanistic aspects of sensitized photodegradation of β-lactam antibiotics: microbiological implications - Reynoso, Eugenia (2012)
Amoxicillin (Amx) and cephalexin (Cfx) are β-lactam antibiotics widely used in human and veterinary medicine. Two points of interest surrounding these molecules are the photodegradation of the molecules and their microbiological implications, as well as the persistence and bioaccumulation in the environment which may cause resistance to bacterial strains. The kinetic and mechanistic aspects of the photosensitized degradation of Amx and Cfx have been studied in water at pH 7.4 and 10 by stationary and time-resolved methods. Kinetic evidence indicates that the Rose Bengal-sensitized photooxidation of Amx at pH 7.4 proceeds via O₂(¹Δg) and O₂.- mechanisms while at pH 10 the degradation path occurs, principally, via O₂(¹Δ,g). For Cfx, this process is attributed to O₂(1Δg) and O₂.-. Photoproducts, which arise from the addition of oxygen atoms and subsequent oxidation of the groups –CH₃ to –COOH, were detected. For both antibiotics the bacteriostatic activity decreases in parallel to their photodegradation. The results of this study could potentially help scientists to better understand and predict the photodegradability of these antibiotics on living organisms and in different environmental compartments.